The distribution of late-Quaternary woody taxa in northern Eurasia: evidence from a new macrofossil database - Binney, H; Willis, K; Edwards, M; Bhagwat, SA; Anderson, P; Andreev, A; Blaauw, M; Damblon, F; Haesaerts, P; Kienast, F; Kremenetski, K; Krivonogov, S; et al. (2009)
We present a database of late-Quaternary plant macrofossil records for northern Eurasia (from 23° to 180°E and 46° to 76°N) comprising 281 localities, over 2300 samples and over 13,000 individual records. Samples are individually radiocarbon dated or are assigned ages via age models fitted to sequences of calibrated radiocarbon dates within a section. Tree species characteristic of modern northern forests (e.g. Picea, Larix, tree-Betula) are recorded at least intermittently from prior to the last glacial maximum (LGM), through the LGM and Lateglacial, to the Holocene, and some records locate trees close to the limits of the Scandinavian ice sheet, supporting the hypothesis that some taxa persisted in northern refugia during the last glacial cycle. Northern trees show differing spatio-temporal patterns across Siberia: deciduous trees were widespread in the Lateglacial, with individuals occurring across much of their contemporary ranges, while evergreen conifers expanded northwards to their range limits in the Holocene. © 2009 Elsevier Ltd. All rights reserved.